Potential of confocal laser scanning microscopy for non-invasive diagnostics of malignant epithelial skin tumors in the course of dermatoheliosis progression - E. S. Snarskaya; S. B. Tkachenko; E. V. Kuznetsova; A. S. Allenova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Most cases of malignant epithelial skin neoplasms including actinic keratosis and basal cell carcinoma, which are characterized by the most complicated course and numerous clinical and morphological options, involve dermatoheliosis progression. The risk of actinic keratosis transformation into basal cell carcinoma varies from 0.1% to 20% and up to 80% in cases of multiple AK lesion foci. A non-invasive method known as reflectance confocal laser scanning microscopy is the most promising one for the purposes of early diagnostics of signs pointing at epithelial skin neoplasm development and makes it possible to monitor the tumor in progress in vivo to diagnose the presence of a pool of squamous cells on a timely basis. The confocal laser scanning microscopy method provides high-contrast images of for any horizontal-oriented morphologic structures in the epidermis and upper dermis with a resolution comparable to those characteristic of traditional optical microscopy of skin tissue samples. According to our data obtained as a result of studying dynamic changes and morphologic structures in actinic keratosis foci (50 cases) using the confocal laser scanning microscopy method, we discovered a number of morphologic features, and their further analysis will distinguish the signs of progressing carcinogenesis in case of dermatoheliosis.